Drosophila melanogaster as a model to study polymicrobial synergy and dysbiosis - Cao, Xixi; Scoffield, Jessica; Xie, Baotong; Morton, David B.; Wu, Hui (Frontiers in Cellular and Infection Microbiology, 2023)
The fruit fly Drosophila melanogaster has emerged as a valuable model for investigating human biology, including the role of the microbiome in health and disease. Historically, studies involving the infection of D. melanogaster with single microbial species have yielded critical insights into bacterial colonization and host innate immunity. However, recent evidence has underscored that multiple microbial species can interact in complex ways through physical connections, metabolic cross-feeding, or signaling exchanges, with significant implications for healthy homeostasis and the initiation, progression, and outcomes of disease. As a result, researchers have shifted their focus toward developing more robust and representative in vivo models of co-infection to probe the intricacies of polymicrobial synergy and dysbiosis. This review provides a comprehensive overview of the pioneering work and recent advances in the field, highlighting the utility of Drosophila as an alternative model for studying the multifaceted microbial interactions that occur within the oral cavity and other body sites. We will discuss the factors and mechanisms that drive microbial community dynamics, as well as their impacts on host physiology and immune responses. Furthermore, this review will delve into the emerging evidence that connects oral microbes to systemic conditions in both health and disease. As our understanding of the microbiome continues to evolve, Drosophila offers a powerful and tractable model for unraveling the complex interplay between host and microbes including oral microbes, which has far-reaching implications for human health and the development of targeted therapeutic interventions.